CONHECENDO MULHERES QUE ENFRENTAM O TRATAMENTO PARA O CÂNCER NA REGIÃO SUL DO BRASIL - Buzanelo, Ana L.; Berlezi, Evelise M.; Giaretta, Maira; Kolankiewicz, Adriane C. B.; Rosanelli, Cleci S. P. (Salão do Conhecimento, 2013)
Resumo